Mechanisms of NAFLD development and therapeutic strategies. (July 2018) - Friedman, Scott; Neuschwander-Tetri, Brent; Rinella, Mary; Sanyal, Arun
Abstract There has been a rise in the prevalence of nonalcoholic fatty liver disease (NAFLD), paralleling a worldwide increase in diabetes and metabolic syndrome. NAFLD, a continuum of liver abnormalities from nonalcoholic fatty liver (NAFL) to nonalcoholic steatohepatitis (NASH), has a variable course but can lead to cirrhosis and liver cancer. Here we review the pathogenic and clinical features of NAFLD, its major comorbidities, clinical progression and risk of complications and in vitro and animal models of NAFLD enabling refinement of therapeutic targets that can accelerate drug development. We also discuss evolving principles of clinical trial design to evaluate drug efficacy and the emerging targets for drug development that involve either single agents or combination therapies intended to arrest or reverse disease progression. Understanding of pathogenic mechanisms and clinical features of NAFLD is driving progress in therapeutic strategies now in clinical trials.